2006
DOI: 10.12968/jowc.2006.15.9.26965
|View full text |Cite
|
Sign up to set email alerts
|

Delays to the definitive surgical management of pretibial lacerations in the elderly

Abstract: Wounds to the pretibial region in the elderly are common and have been estimated to account for 5.2 per 1000 emergency department attendances.1 In this patient population, such an injury can precipitate a rapid decline in mobility and independence. Minimising the period of immobility associated with such an injury has been shown to reduce this effect.2 In many cases this is best achieved through early debridement and split skin-graft coverage. However, unacceptable delays often occur in the care pathway of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…Patients who sustain pretibial injuries are predominantly frail, elderly females with medical co-morbidities [16], as reflected in our data (55 females: 14 males). This is a very similar demographic as patients who sustain fractures of the proximal femur.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Patients who sustain pretibial injuries are predominantly frail, elderly females with medical co-morbidities [16], as reflected in our data (55 females: 14 males). This is a very similar demographic as patients who sustain fractures of the proximal femur.…”
Section: Discussionsupporting
confidence: 65%
“…A review of literature pertaining to timing of surgery suggests that this is dependent upon timing of presentation after injury, whether initial conservative treatment has been trialled, the patient condition, and delays. It is not unreasonable to trial conservative management in the very first few days after injury [16]. This allows demarcation of viable from non-viable tissue.…”
Section: Discussionmentioning
confidence: 99%
“…3 A prospective study on the surgical management of pretibial lacerations reported a cancellation rate of 50%, overall starvation time of 18 hours and a delay between referral and surgery of 10 days. 15,16 Tubuku- Metzger et al 11 reviewed all patients admitted to their tertiary plastic surgery centre and found that delay in surgery had significant effects on outcome. These figures must be reduced if patient outcomes are to be improved.…”
Section: Discussionmentioning
confidence: 99%